El determinismo tecnológico a la luz de la Filosofía de la Tecnología - Casquier Ortiz, Jesús Rodomiro (2019)
The article proposes a panoramic vision about the phenomenon of technological determinism as an initial point to assumptions and ideas about the question. Is it possible to talk about technological autonomy? He postulates that, although some scholars have developed some philosophical reflections in the field of Technology Philosophy, the advances that have been made since the philosophical reflection on this discipline and its links with the social and cultural progress of beings are still incipient humans.